THE RATIONALE FOR PLATELET-RICH PLASMA (PRP) THERAPY IN CHRONIC WOUNDS : SYSTEMATIC REVIEW - Kresna Mahayana, I Gede Arya; Ariandana, Ika (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Chronic wounds are common and reduce quality of life. The financial burden of dressing materials, amputation costs, and the ongoing and extended need for human resources to treat wounds affects healthcare resource utilization. Platelet-rich plasma (PRP) has been shown to increase the healing rates of open diabetic foot ulcers and venous ulcers. The aim: This article demonstrated the rationale for platelet-rich plasma (PRP) therapy in chronic wounds. Methods: This study demonstrated that it met all of the requirements by comparing itself to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. As a result, the specialists were able to ensure that the study was as up to date as possible. Publications published between 2013 and 2023 were considered for this search strategy. This was accomplished using a variety of online reference sources, including Pubmed and SagePub. It was chosen not to include review pieces, previously published works, or works that were just partially completed. Result: In the PubMed database, the results of our search brought up 76 articles and SagePub 62 articles. The results of the search conducted for the last year of 2013 yielded a total 16 articles for PubMed and 12 articles from SagePub. In the end, we compiled a total of six papers. Conclusion: PRP is composed of several components obtained from platelets, including growth factors and cytokines. These bioactive substances have a significant role in modulating processes such as inflammation, angiogenesis, stem cell activity, and cellular proliferation.